Challenges of the tourism sector in Lithuania in the context of the COVID-19 pandemic: State aid instruments and the efficiency of the tourism business support - Pociute-Sereikiene, Gintare; Baranauskienė, Viktorija; Liutikas, Darius; Kriaučiūnas, Edis; Burneika, Donatas (European Spatial Research and Policy, 2024)
At the beginning of 2020 Lithuania, and many other European countries, introduced quarantine and began restricting movement across the country’s borders. The imposed restrictive measures have greatly impacted and led to the stagnation of tourism sector. Due to the COVID-19 pandemic and travel restrictions, the number of international tourist arrivals sharply decreased. In 2021 the majority of restrictions have been eased due to the decreasing morbidity, but it did not reinstate the tourism into the previous level. According to statistics, the decline in tourist flows in Lithuania in 2021 still continued, albeit the decrease was smaller. The increase in the number of local tourists (especially in 2021) has somewhat compensated the loss of international tourism, but has not changed it. The tourism business is still going through a difficult period. This article emphasizes the issues of local and inbound tourism business in Lithuania in the context of Covid-19 pandemic. The greatest attention is placed on the instruments proposed by the Lithuanian Government to mitigate the negative consequences of the pandemic on tourism service. The research combines secondary and primary data sources. Secondary data was used for the analysis of official Lithuanian statistics in order to introduce general trends of the development of tourism sector during the last decade. Primary data was received using the methods of focus group and survey (a questionnaire to collect data sets from tourism business enterprises in Lithuania). The statistical analysis revealed that the difficult situation was noticed in all fields of tourism sector, however, the main losers of the pandemic were those relying on the international tourist. The analysis of official documents disclosed, that even though the tourism business was able to benefit from the variety of offered governmental aid packages in 2020–2021, the quantity and quality of support was not enough and strongly criticized. Our survey results pointed out the instruments that were most effective among the tourism enterprises. Moreover, from the collected answers we noticed, that at least part of tourism enterprises took the opportunity to use the support not only for compensation of pandemic related costs but also to look forward and the received financial support invested in innovative solutions in the tourism business, so pandemic potentially had some positive effects as well. Also, the survey results reviled that there are considerable opportunities for tourism related development of the nature rich, non-metropolitan regions, though at the moment these activities quite often remain outside the market relations and do not produce new incomes and jobs.